Accounting and auditing through the lens of non-accountants: an emerging economy experience / Ibrahim Khan and Md. Shafiqul Islam - Khan, Ibrahim; Islam, Md. Shafiqul (Accounting Research Institute (ARI), 2020)
Both accounting and auditing involve public interest and so it is important to understand the legitimacy of these fields from the point of view of the non-accountants. Therefore, this study looks at the perception of accounting among non-accountants; status of non-accounting users' understandability of accounting information; and finally, perception of non-accountants about the effectiveness of audits. Using 33 semi-structured interviews to draw common factors in the first stage and conducting a questionnaire survey among 125 participants to test the consistency of the interview results in the second stage, this study found that non-accountants, in general, view accounting as an excessively technical, less forward-looking and number crunching discipline. This study also found that non-accountant investors lack understanding of accounting reports and metrics, make trading decisions based on other sources of information and have low level of faith in accounting numbers. However, the comparability feature of accounting information tends to offset some of the decision-making barriers. Another finding of this study is that the credibility of audit reports, in general, is low among non-accountants. The role of an audit is considered an ornamental exercise. The findings show that awareness about accounting and auditing is relatively low in Bangladesh suggesting a small number of "informed users".